Severe Hypoglycemia in Type II Diabetes at Nakornping General Hospital: A study on Clinical Risk Factors - Tippaya Sanchai (2018)
Objective: To study clinical risk factors of severe hypoglycemia in type II diabetes Material and Method: Fifty-one type II diabetes with severe hypoglycemia admitted between October 2006 and September 2008 and 359 nonhypoglycemic type II diabetes were evaluated in this case-control study. Medical records were retrospective reviewed for age, sex, duration of diabetes, previous diabetes registration, concomitant diseases, HbA1c level and current diabetes therapy in both groups. Acute illness, blood glucose, hypoglycemic episodes, symptoms and length of stay (LOS) were assessed in hypoglycemic group. Univariate and multivariate logistic regression were used to determine risk factors of severe hypoglycemia. Results: Fifty-one hypoglycemic and 359 nonhypoglycemic patients were analyzed. The authors found that 40% of severe hypoglycemic cases were recurrent. The average LOS was six days. Intercurrent illness was the major leading cause of hypoglycemia (54.9%). Mean blood glucose level was 37.2 mg/dl (SD = 13.5). Twenty-three of fifty-one (45%) patients presented with unconsciousness. Predisposing risk factors associated with severe hypoglycemia were old age (p = 0.026), insulin therapy (p = 0.001), cirrhosis (p = 0.020), cerebrovascular disease (p = 0.040), and no diabetes registry (p = 0.015). Sex, HbA1c level, hypertension and chronic kidney disease were not risk factors associated with severe hypoglycemia. Conclusion: Risk factors associated with severe hypoglycemia in type II diabetes were elderly, insulin therapy, cirrhosis, previous cerebrovascular disease, lack of standard diabetic care and team approach. Self-monitoring of blood glucose and individual case management should be considered in those with previous hypoglycemic events.